Knowledge about the rncci: an exploratory study about the perception of nursing students - Gonçalves, Ana Rita Veloso (2016)
The National Network of Continuing Care (RNCCI) was created in 2006 by Decree Law nr. 101/2006. Its mission is to supply adequate health and social care to all people who, independent of their age, are in a situation of dependence, and its action is articulated with the already existing health and social services, being a multidisciplinary team needed composed out of medical doctors, nurses, social workers and psychologists. Given the aforementioned it’s pertinent to perform research, with nurses and nursing students, about this new valence of care.